Influence of fat and monensin levels on performance of finishing steers - Brandt, Robert T., Jr.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
To evaluate effects and potential interaction of supplemental fat (0 to 4% tallow) and monensin (0, 20, 40 g/ton) in a corn-based finishing diet, 96 Continental crossbred steers (860 lb) were used in a 2×3 factorially arranged randomized complete block design. Consumption by steers fed the 0% fat diet decreased linearly (P<.0001) with increased monensin level, whereas consumption by steers fed 4% fat diets decreased curvilinearly (P<.08), indicating that monensin depressed intake much less when the diet contained fat. Daily gain decreased linearly (P<.02) with increased monensin level for steers fed no supplemental fat, but remained constant in steers fed 4% fat. Feed efficiency was improved (P<.025) by 4% fat across levels of monensin. This study provides further evidence of interactions between monensin and supplemental fat in effects on animal performance.
Keywords: Beef; Fat; Monensin; Feedlot; Performance